2018
DOI: 10.1108/jaar-11-2014-0122
|View full text |Cite
|
Sign up to set email alerts
|

Small business social responsibility: the CSR4UTOOL web application

Abstract: Purpose Small and medium-sized enterprises (SMEs) positively represent the backbone of the European economic system and, negatively, they make a significant contribution to environmental pollution and social impacts. The purpose of this paper is to discuss how a new tool for supporting the adoption of small business social responsibility (SBSR) can be tailored in order to be more effective. Design/methodology/approach Theoretical framework – a literature analysis of how SMEs address sustainability issues wil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 91 publications
1
9
0
2
Order By: Relevance
“…Our analysis confirms the interest by SMEs to inform stakeholders about their environmental practices since this has become important for improving their competitive performance (Corazza, 2018), as well as also shows their interest in CE disclosure as a relevant aspect to address in the sustainability reporting activities (Scarpellini, 2022). To Circular economy strategies disclosure this regard, our results show that SMEs are implementing CE strategies related to both closing and slowing resource loops (Bocken et al, 2016).…”
Section: Discussionsupporting
confidence: 78%
“…Our analysis confirms the interest by SMEs to inform stakeholders about their environmental practices since this has become important for improving their competitive performance (Corazza, 2018), as well as also shows their interest in CE disclosure as a relevant aspect to address in the sustainability reporting activities (Scarpellini, 2022). To Circular economy strategies disclosure this regard, our results show that SMEs are implementing CE strategies related to both closing and slowing resource loops (Bocken et al, 2016).…”
Section: Discussionsupporting
confidence: 78%
“…As found in other studies, our results suggest that bigger organizations tend to conduct more sophisticated sustainability disclosure and consequently are more likely to integrate the SDGs into their reporting because of legitimacy (Wickert et al , 2016). Therefore, research is needed about how to increase the likelihood of addressing the SDGs for smaller reporting entities or more in general about tools that increase SMEs sustainability reporting (Corazza, 2018). The same is true for reporting entities that are not publicly listed.…”
Section: Conclusion Limitations and Future Researchmentioning
confidence: 99%
“…It is evident that the inclusion of relative data through indicators is understood as very relevant to the quality of the results aimed at sustainable development in the small municipalities that are the object of this proposal (Réus & Andion, 2018). It is also observed that there is a gap to be filled in the knowledge and dissemination of these tools (Corazza, 2018), with a view to the effectiveness of public policies and the consequent improvement of the environmental, social, and economic aspects obtained through the decision making of managers public data based on concrete data in these municipalities (Réus & Andion, 2018).…”
Section: Data Presentation and Analysismentioning
confidence: 99%